Reduplikasi Antar Bahasa Gayo Dengan Bahasa Indonesia - Cibro, Juniara Fitri (Jumper: Journal of Educational Multidisciplinary Research, 2022)
Abstrack The research entitled "The Reduplication in Gayo Language" has examined: (1) what are the forms of reduplication in Gayo language, (2) what types of words are reduplicated in Gayo language, and (3) what meaning is contained in Gayo language reduplication. The objective of this study were: (1) to describe the forms of Gayo language reduplication, (2) to describe the types of words which are reduplicated in Gayo language, and (3) to describe the meaning contained in Gayo language reduplication. The data source for this research are some native speakers of the Gayo language in Kebayakan. By using descriptive qualitative, Data collection was taken through observation, interview, recording, and reflection. The results of the study showed that the reduplication in Gayo language is generally as same as the reduplication of the Acehnese language. There were four forms of Gayo language reduplication found, namely: (1) full reduplication, (2) sound-changing reduplication, (3) partial reduplication, and (4) affixed reduplication. All words in the Gayo language had reduplication forms, especially full reduplication. Sound- changing reduplication occurs in verbs and adjectives. Partial reduplication occurs in verbs, nouns, adjectives, adverbs, and numerals. Affixed reduplication occurs in verbs, nouns, and adjectives. In the Gayo language, a form of sound-changing reduplication is found only in the word lintang-lintu. In affixed reduplication, it is found that the prefix -mu attached to the basic word gelumang becomes mugelumang and it was reduplicated become mugegelumang. Then to it appeared as two forms, gelumang → gelumang-gelumang → mugelumang-mugelumang → mugegelumang and gelumang → gelumang-gelumang → gegelumang → gegelumang-gegelumang → mugegelumang. In addition, there is also a prefix ¬i¬ in reduplication such as ipanang-ipanang, ipeltek-peltek, itatang-tatang, and ipies-pies which can also be used in other forms such as ipepanang, itetatang, and ipepies. Keywords: reduplication, Gayo language